A STUDY ON THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON COMMUNICATION EFFECTIVENESS AND ANXIETY MANAGEMENT TOWARD ORGANISATIONAL CHANGE - Nandy, Dr. Sarmistha; George, Aswin (IJRDO - Journal of Business Management, 2016)
Over the last few decades there has been incredible development in Emotional Intelligence research. It has been erudite that since Emotional Intelligence is not only anattribute, Emotional Intelligence is acrucialaspect to be reflected in an organizational arrangement. The correlation between emotional intelligence, communication efficacy plays a vigorous role in the progression and achievement of an organisation set up. Work anxiety will be occurred amongst individuals when they feel extreme burden about imminent and prior incidence. Individuals’ with high level of anxiety,maximum of the time misconstrued or exaggerated the significance of the situation. If the state is not accomplisheddecorously,damagingpenalties may happen. In addition, individual that display emotional intelligence toward diversestuffs can growth their expertise in any work situation. The purpose of the present study is to enhance a different way of looking on organisational change by concentrating on individual’s emotion and behaviour traits.